Process optimization and evaluation of quality properties of natto with co-culture of Bacillus subtilis natto and Limosilactobacillus fermentum - Yi-Ni Ma; Xun Xu; Lai-Feng Chen; Jin-Ping Zhou; Zhen-Hui Cao; Qiu-Ye Lin (Current Research in Microbial Sciences)
The present study aimed to optimize the processing technology of natto fermented with Bacillus subtilis natto and Limosilactobacillus fermentum 2–2 and its effect on quality characteristics as well as volatile compounds. The results of single-factor tests and response surface methodology (RSM) showed that the optimal fermentation conditions of natto were L. fermentum inoculation amount of 0.3 %, fermentation temperature at 39 °C, fermentation time of 48 h, and after-ripening time of 24 h. Compared with natto control with B. subtilis natto only, natto co-cultured with B. subtilis natto and L. fermentum 2–2 showed higher scavenging ability of 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and greater nattokinase activity. Volatomics analysis revealed that 71 differential volatile compounds were identified with 23 up-regulated and 48 down-regulated. Especially, co-fermentation of B. subtilis natto and L. fermentum 2–2 increased generation of alcohols, ketones and esters while reduced pyrazines formation. The above results indicate that co-culture of B. subtilis natto and L. fermentum can enhance the antioxidant and nattokinase activity and modify the volatile profile in natto and have the potential for application as the mixed starter in natto production.